Three cases of worker mobilization in contemporary Turkey - Birelma, Alpkan. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2007., 2007)
This thesis examines three cases of contemporary worker mobilizations with the aim of unionization in Turkey. Special emphasis is devoted to the investigation of the participant workers’ experiences and agency. It is argued that there is an ever-present temptation to objectify and distance the working class due to the unequal power relations in our global society. Thanks to the rise of neo-liberalism at the ideological level and the concomitant rise of post-fordism, this temptation has become even stronger, in line with the fact that the extent of the rule of the capital has strengthened itself. Hence workers’ experiences have become degraded, and their agency neglected. The investigation of three mobilizations reveals the particular difficulties the workers faced on the way to unionization due to the legal restrictions and the economic conditions as can be seen in high rates of unemployment and low job security. Emphasis is given to the ways in which workers attempted to overcome the mentioned difficulties by way of workers’ agency. The data consists of observations made during the mobilizations and afterwards, and the detailed interviews with the participants. How those workers perceived and expressed their experiences, as necessarily it is, in cultural terms is especially scrutinized, following E. P. Thompson’s inspiring contributions. This thesis illuminates the workers’ agency, and focuses on the more indigenous worker strategies, cultural practices and active work-group social relations such as the formation of solidarity, cohesion and networks among workers, instead of focusing on the external factors, such as union involvement, or pure economic factors on which conventional works mainly concentrate.
Keywords: Labor movement -- Turkey.; Working class -- Turkey.